2009
DOI: 10.1111/j.1600-0404.2009.01270.x
|View full text |Cite
|
Sign up to set email alerts
|

Focal clinical and electroencephalographic features in patients with juvenile myoclonic epilepsy

Abstract: Patients with JME showed focal clinical and EEG features. These features should not be misinterpreted as indicative of partial epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
47
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 30 publications
1
47
0
3
Order By: Relevance
“…In other studies also noncompliance with AEDs has been an important factor contributing to lack of seizure control [8]. Various studies have found comorbid psychiatric or personality disorders in patients with JME and this has been suggested to be one of the reasons for noncompliance of AEDs [9, 13, 16]. Approximately half of our patients were not aware of the important lifestyle modifications required for JME, mainly taking adequate sleep and avoiding sleep deprivation, leading to breakthrough seizures.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In other studies also noncompliance with AEDs has been an important factor contributing to lack of seizure control [8]. Various studies have found comorbid psychiatric or personality disorders in patients with JME and this has been suggested to be one of the reasons for noncompliance of AEDs [9, 13, 16]. Approximately half of our patients were not aware of the important lifestyle modifications required for JME, mainly taking adequate sleep and avoiding sleep deprivation, leading to breakthrough seizures.…”
Section: Discussionmentioning
confidence: 81%
“…Focal clinical and EEG abnormalities are not uncommon in JME as found in a study from India and this can be a major reason for misdiagnosis in JME [13]. If the treating physician is not well-experienced in epilepsy care and not aware of the fact that focal findings can occur in JME, such abnormalities would often lead to misdiagnosis of focal epilepsy, leading to use of carbamazepine or oxcarbazepine, which would not be effective in JME, leading to lack of control of seizures [13, 14]. A sleep deprived EEG definitely increases the sensitivity of EEG records, but in private clinical practice patients often undergo the tests immediately after the outpatient consultation and are not called for sleep deprived EEG on another day.…”
Section: Discussionmentioning
confidence: 99%
“…The epileptiform activity in JME is typically generalized 4–6 Hz spike‐wave (SW) activity (Pedersen & Petersen, 1998). However, one third of patients with JME may have subtle focal electroencephalography (EEG) abnormalities, sometimes associated with focal semiologic features (Usui et al., 2005; Jayalakshmi et al., 2010).…”
mentioning
confidence: 99%
“…These findings tend to be intermittent and shifting in laterality. 15,[23][24][25] Densearray EEG analysis of patients with absence epilepsy demonstrated ictal onsets, often unilateral, arising from the dorsolateral frontal or orbital frontal lobe followed by stereotyped evolution to involve both mesial frontal and orbital frontal structures. 26 Auras and other "focal" features in patients with GE can lead to the misdiagnosis of FE.…”
mentioning
confidence: 99%